Takotsubo Cardiomyopathy Triggered by MRI-Induced Fear and Anxiety - Ahmed Hassaan Qavi; Andreea Constanta Stan; Ateet Kosaraju; Rony L. Shammas (Case Reports in Cardiology)
Takotsubo cardiomyopathy (TC), or ‘broken heart syndrome,’ is marked by transient left ventricular dysfunction in the absence of acute, severe coronary artery disease that explains the pattern and degree of LV dysfunction. Both emotional and physical stressors have been associated with TC. We present a case of TC that was precipitated by a routine magnetic imaging resonance scan, highlighting a rare and previously unreported trigger for TC.